Stability and inflation : a volume of essays to honour the memory of A.W.H. Phillips - Bergstrom, A. R.; New Zealand Association of Economists (Chichester ; New York : Wiley, 1978)
This book contained most of the essays in honour of the memory of Professor A.W.H. Phillips which' were assembled as a Festschrift to mark his sixtieth birthday on 18th November 1974.
Includes bibliographical references and index.
osa 06/08/2018
Loans
Keywords: Phillips, A. W. H; Inflation (Finance); Phillips curve; Economic stabilization